The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.7861/clinmedicine.17-6-525
|View full text |Cite
|
Sign up to set email alerts
|

The lung microbiome in health and disease

Abstract: The Human Microbiome Project began 10 years ago, leading to a signifi cant growth in understanding of the role the human microbiome plays in health and disease. In this article, we explain with an emphasis on the lung, the origins of microbiome research. We discuss how 16S rRNA gene sequencing became the fi rst major molecular tool to examine the bacterial communities present within the human body. We highlight the pitfalls of molecular-based studies, such as false fi ndings resulting from contamination, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(110 citation statements)
references
References 47 publications
3
98
0
3
Order By: Relevance
“…Our results reinforce the previously known particularities of the lung microbiota, which considerably differ from oral and stool microbial communities [29]. One important concern is the theoretical risk of contamination with the upper microbiota during the bronchoscopy, but our results allowed us to rule out significant contamination, as other authors had previously suggested [30][31][32]. Data analysis by various methodologies highlighted the particularities of the microbiota associated with cancer, but also defined the respiratory microbiota core in healthy conditions.…”
Section: Discussionsupporting
confidence: 87%
“…Our results reinforce the previously known particularities of the lung microbiota, which considerably differ from oral and stool microbial communities [29]. One important concern is the theoretical risk of contamination with the upper microbiota during the bronchoscopy, but our results allowed us to rule out significant contamination, as other authors had previously suggested [30][31][32]. Data analysis by various methodologies highlighted the particularities of the microbiota associated with cancer, but also defined the respiratory microbiota core in healthy conditions.…”
Section: Discussionsupporting
confidence: 87%
“…We found that, in addition to Staphylococcus nepalensis strain CNDG, sequences similar to corisin are highly conserved in several transglycosylases from other Staphylococcus species and some members of the microbial community that inhabit the normal or fibrotic lungs, including strains of Streptococcus pneumoniae and Mycobacterium abscessus 51,[58][59][60] . This observation suggests that a broad range of bacteria may be the source of corisin in pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 95%
“…To date, the majority of metagenomic sequencing assays have targeted amplicons within the 16S or 28S rRNA subunits, allowing detection of pulmonary bacteria or fungi, but not both, and not viruses [31]. Recently, unbiased mNGS assays have allowed detection of both bacterial and viral nucleic acid but have lacked ideal sensitivity for detecting filamentous mold [11,12].…”
Section: Discussionmentioning
confidence: 99%